Chiral phosphine-catalyzed tunable cycloaddition reactions of allenoates with benzofuranone-derived olefins for a highly regio-, diastereo- and enantioselective synthesis of spiro-benzofuranones. Issue 12 (2nd October 2015) - Wang, De; Wang, Guo-Peng; Sun, Yao-Liang; Zhu, Shou-Fei; Wei, Yin; Zhou, Qi-Lin; Shi, Min
Abstract : The first regioselective catalytic asymmetric [3 + 2] cycloaddition of benzofuranone-derived olefins with allenoates and substituted allenoates has been developed in the presence of ( R )-SITCP. Abstract : The first regioselective catalytic asymmetric [3 + 2] cycloaddition of benzofuranone-derived olefins with allenoates and substituted allenoates has been developed in the presence of ( R )-SITCP, affording different functionalized 3-spirocyclopentene benzofuran-2-ones in good yields with high enantioselectivities under mild conditions. The substrate scope has also been examined. The regioselective outcomes for this phosphine-catalyzed [3 + 2] cycloaddition reaction can be rationalized using DFT calculations.